The product of self-deception: A critical analysis of N. Van Leeuwen’s proposal. - Vorano, Agostina (Analysis. Journal of Philosophical Research, 2023)
Self-deception is an intriguing and complex phenomenon, which has been extensively discussed in the philosophical field. There is a widespread lack of consensus regarding most of its aspects; however, there is one thesis which is widely accepted: the idea according to which the product of self-deception is a belief. Many of the authors who have accepted this thesis implicitly take for granted that it is not necessary to carry out a systematic analysis of the characteristics of this propositional attitude. This seems to be due to the fact that they judge that it consists on a folk-psychological concept and that, as such, it can be intuitively and automatically comprehended. We consider that this constitutes an argumentative deficit, and we present a possible source of this deficit. Afterwards, we analyze the ideas advanced by a prolific contemporary author, N. Van Leeuwen, because we consider that his proposal overcomes this deficit. However, his perspective is affected by some difficulties; we identify and examine them, and we conclude that, because of them, Van Leeuwen is not able to satisfactorily answer the question about the product of self-deception. Finally, we present three possible answers to this question, highlighting the virtues of the third answer.